Analisis Keterampilan Komunikasi dalam Pembelajaran IPS di SD - Roseli Amanda; Erlisnawati Erlisnawati; Otang Kurniaman (Jurnal Educhild : Pendidikan dan Sosial, 2022)
The purpose of this study was to determine the level of students' oral communication skills in social studies learning in elementary school. This research is a qualitative descriptive study in which research data were collected through interview techniques and social studies learning video documentation which were then analyzed. Based on the results of the study, it was found that the level of students' oral communication was in the good range with a percentage score of 67%. students are able to answer questions briefly and precisely but take a long time, students conclude learning but are still not precise, students are able to make presentations fluently but are still shy, students speak using a medium volume of voice, students speak using language that can be understood but is less effective, students pay attention to the interlocutor but occasionally chat, students do not interrupt the interlocutor's conversation but do not listen to the interlocutor's conversation, students distinguish how to talk to their teachers and friends but do not know the right situation to speak, students speak in a good and polite language and do not mock their friends , and students speak Indonesian but occasionally use village language during the learning process.Tujuan dari penelitian ini adalah untuk mengetahui tingkat keterampilan komunikasi lisan siswa dalam pembelajaran IPS di SD. Penelitian ini merupakan penelitian deskriptif kualitatif yang mana data penelitian dikumpulkan melalui teknik wawancara dan dokumentasi video pembelajaran IPS yang kemudian di analisis. Berdasarkan hasil penelitian diperoleh tingkat komunikasi lisan siswa berada pada rentang baik dengan persentase skor 67%. siswa mampu menjawab pertanyaan dengan singkat dan tepat tetapi agak lama, siswa  menyimpulkan pembelajaran tetapi masih kurang tepat, siswa mampu melakukan presentasi dengan lancar tetapi masih malu-malu, siswa berbicara menggunakan volume suara sedang, siswa berbicara menggunakan bahasa yang dapat dipahami tapi kurang efektif, siswa memperhatikan lawan bicara tetapi sesekali mengobrol, siswa tidak memotong pembicaraan lawan bicara tetapi kurang mendengarkan pembicaraan lawan bicara, siswa membedakan cara bicara terhadap guru dan temannya tetapi kurang mengetahui situasi yang tepat untuk berbicara, siswa berbicara dengan bahasa yang baik dan sopan sertas tidak mengejek temannya, dan siswa berbicara menggunakan bahasa Indonesia tetapi sesekali menggunakan bahasa kampung saat proses pembelajaran.